Knowledge and preferences among independent smallholders in adopting Malaysian Sustainable Palm Oil (MSPO): case of Melaka / Syed Ammar Ashraff Syed Mohammad Nasser - Syed Mohammad Nasser, Syed Ammar Ashraff (Faculty of Plantation and Agrotechnology, 2018)
Nowadays, the current issue in oil palm plantation management is how to ensure the sustainability production of palm oil product without neglect of environmental and future concern. This study is focus on independent smallholders which is 16.9% which play prominent contribution in Malaysian palm oil industry. In order to address these issues is by adoption of Malaysia Sustainability Palm Oil (MSPO) by independent smallholders. Regarding that matter, these study aim to estimate knowledge among smallholders in adopting MSPO. Besides, this survey is to determine smallholder’s preferences that influencing them to adopt sustainability certification (ISCC, RSPO, MSPO). This study also is to determine the most dominant factor that influences adoption of MSPO. Total respondent of this research is 45 respondents which is independent smallholders and conducted in 2 different regions in Melaka which is Machap and Sungai Rambai. Based on results, shows that relationship between knowledge and adoption of MSPO among independent smallholders is strong. Relationship between preferences and adoption of MSPO among independent smallholders also shows a strong relationship.